2019
DOI: 10.1186/s13047-019-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

The foot‐health of people with diabetes in regional and rural Australia: baseline results from an observational cohort study

Abstract: BackgroundThere is limited Australian epidemiological research that reports on the foot-health characteristics of people with diabetes, especially within rural and regional settings. The objective of this study was to explore the associations between demographic, socio-economic and diabetes-related variables with diabetes-related foot morbidity in people residing in regional and rural Australia.MethodsAdults with diabetes were recruited from non-metropolitan Australian publicly-funded podiatry services. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 38 publications
8
23
1
Order By: Relevance
“…The prevalence of DPN was also found to be higher among DM patients who were having diabetes for more than 10 years. This was in line with results of previous studies [13], [14], [17], [20]. As the duration of DM increases, the risk of complications advances and this accelerates if the glycemic control is also poor.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of DPN was also found to be higher among DM patients who were having diabetes for more than 10 years. This was in line with results of previous studies [13], [14], [17], [20]. As the duration of DM increases, the risk of complications advances and this accelerates if the glycemic control is also poor.…”
Section: Discussionsupporting
confidence: 92%
“…About 42.0% of diabetic patients were found to be suffering from peripheral neuropathy. This was similar to the ndings of other studies on diabetic peripheral neuropathy (DPN) [10], [13][14][15][16].However, this was in contrast to the ndings of Kaewput et al [17] and Perrin et al [18] in which prevalence ranged from 3.0% to 16.6%. The possible reasons for this variation could be different study settings and different classi cation used to diagnose DPN in these studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While the relevant global guidance and clinical pathway publications directly describe the best available evidence base for assessment, diagnosis and management of acute CN, little attention has been given to factors that may impact on the delivery of this care [ 1 , 3 , 4 , 42 ]. This finding is not surprising because the biopsychosocial barriers influencing foot-health outcomes in people with diabetes and potentials barriers to translating evidence into practice is only recently gaining attention [ 44 , 45 ]. This is particularly concerning as acute CN has been described as a medical emergency, where treatment can be very effective in mitigating pathophysiological deterioration and subsequent gross structural and functional damage to the foot [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with the results of previous studies as well. 10,16 In all such instances where glycemic control is poor, the duration of DM increases the risk of complications and accelerates them too. Ratzman et al observed a quite lower prevalence of diabetic neuropathy (6.3%) in their study.…”
Section: Discussionmentioning
confidence: 99%